Cathodic protected Mn2+ by NaxWO3 nanorods for stable magnetic resonance imaging-guided tumor photothermal therapy. (March 2020) - Liu, Yang; Wu, Shiman; Liu, Yanyan; Zhang, Hua; Zhang, Meng; Tang, Zhongmin; Wang, Yan; Gong, Teng; Yao, Zhenwei; Fang, Xiangming; Bu, Wenbo
Abstract: The stability and safety of magnetic resonance imaging (MRI) contrast agents (CAs) are crucial for accurate diagnosis and real-time monitor of tumor development. Paramagnetic Mn 2+ as nonlanthanide metal ion has been widely studied for use in T 1 -MRI CAs, but unfortunately, Mn 2+ can be oxidized by H2 O2 in tumor to nonparamagnetic Mn 4+ via a Fenton-like reaction. The concurrent loss of paramagnetism and production of toxic hydroxyl radical (OH) go against the basic requirment of CAs, thus restricting the further development of Mn 2+ -based CAs. Based on the different standard potential of W 6+ /W 5+ (~0.26 V) and Mn 4+ /Mn 2+ (~1.2 V), a "cathodic protection" strategy was exploited in Mn 2+ -doped Nax WO3 nanorods (Nax MnWO3 ), with W 5+ as the sacrificial anode and Mn 2+ as the protected cathode, to protect Mn 2+ from oxidation in tumor for stable MR contrast performance, as well as repress its Fenton-like reaction activity for good biosafety. Moreover, the tungsten bronze crystal structure endows Nax MnWO3 with excellent near-infrared (NIR)-photothermal properties for effective tumor hyperthermia, without effect from the changed oxidation state of W. This "cathodic protection" strategy offers a new method for the development of reliable and hypotoxic biomaterials for stable imaging and therapeutic applications in clinic.